Pengaruh Religious Commitment dan Islamic Physical dan Non Physical Attributes terhadap Customer Loyalty dengan Mediasi Customer Satisfaction pada Masyarakat Beragama Islam yang Berkunjung ke Luar Negeri - Angeline Suwandi; Hetty Karunia Tunjungsari (Universitas Tarumanagara, 2021)
This research was conducted with the aim to examine the effects between the variables of religious commitment and Islamic attributes to customer satisfaction as a mediating variable with customer loyalty. The sample of this study is the Muslim community who have visited abroad and are domiciled in JABODETABEK. Data was collected through a survey using a questionnaire. The respondents obtained were 201 respondents with a purposive sampling technique. The data processing method uses PLS-SEM which is assisted by smartPLS 3.0 software. The results showed that religious commitment had no significant effect on Islamic physical attributes and significant variables on Islamic non-physical attributes and customer satisfaction. The two indicators contained in Islamic physical attributes each have a significant and insignificant role on customer satisfaction, while the Islamic non-physical attribute variable has a significant effect on customer satisfaction. Customer satisfaction may act as a good mediator between religious commitment and Islamic physical attributes on customer loyalty. Penelitian ini bertujuan untuk menguji pengaruh religious commitment dan islamic attributes terhadap customer satisfaction sebagai variabel yang memediasi dengan customer loyalty. Objek penelitian ini adalah masyarakat beragama Islam yang pernah berkunjung keluar negeri dan berdomisili di JABODETABEK. Data dikumpulkan dengan menggunakan kuesioner kepada sebanyak 201 responden dengan menggunakan teknik purposive sampling. Metode analisis data menggunakan PLS-SEM yang dibantu oleh software smartPLS 3.0. Hasil penelitian menunjukkan bahwa religious commitment memiliki pengaruh tidak signifikan terhadap variabel islamic physical attributes dan berpengaruh signifikan terhadap islamic non physical attributes serta customer satisfaction. Dua indikator yang terdapat dalam islamic physical attributes masing-masing berperan signifikan dan tidak signifikan terhadap customer satisfaction, sedangkan variabel islamic non physical attributes berpengaruh signifikan terhadap customer satisfaction. Customer satisfaction dapat berperan sebagai mediator yang baik antara religious commitment dan islamic physical attributes terhadap customer loyalty.